Peran Kredit Usaha Rakyat (KUR) terhadap Perkembangan UMKM (Studi Kasus Bank BRI Unit Kedaton) - Khoiriah, Nisaul; Yusda, Desi Derina; Oktaria, Eka Travilta; Hairudin, Hairudin (Penerbit Goodwood, 2024)
Purpose: This study aims to determine the role of people’s Business Credit on the Development of MSMEs at Bank BRI Unit Kedaton. Methodology/approach: This study used qualitative descriptive methods with primary data sources, namely survey and questionnaire results, and secondary data in the form of journals and articles related to research. Data collection techniques included observation, questionnaires, and documentation. The population used in this study is all KUR customers at Bank BRI Unit Kedaton from to 2020-2022 with a sample of 97 respondents calculated using the Cohcran formula. Results: The results of this study show that the role of KUR has a significant effect on the development of MSMEs in the Kedaton Unit, judging from the t-count test results of 9,708 t-tables > 1,661, and from the determinant test results of 49.8%, and the remaining 50.2% was influenced by other var iabels that were not studied in this study. Limitations: This study used only one independent research variable that affected micro, small, and medium-sized enterprises. There are many other independent variables that can explain and possibly influence Micro, Small and Medium Enterprises variables, but researchers did not use them in this final project study. Contribution: The provision of people’s Business Credit (KUR) financing to Micro, Small and Medium Enterprises (MSMEs) is expected to continue to increase so that the wider community can conveniently build or develop a business. Novelty: novelty in this study lies in the time and conditions carried out by the researcher, so as to get differences from the results of the study.